The Global Posttranscriptional Regulator RsmA Modulates Production of Virulence Determinants and N-Acylhomoserine Lactones in Pseudomonas aeruginosa - Pessi, Gabriella (American Society for Microbiology, 2001)
Posttranscriptional control is known to contribute to the regulation of secondary metabolism and virulence determinants in certain gram-negative bacteria. Here we report the isolation of a Pseudomonas aeruginosa gene which encodes a global translational regulatory protein, RsmA (regulator of secondary metabolites). Overexpression of rsmA resulted in a substantial reduction in the levels of extracellular products, including protease, elastase, and staphylolytic (LasA protease) activity as well as the PA-IL lectin, hydrogen cyanide (HCN), and the phenazine pigment pyocyanin. While inactivation of rsmA in P. aeruginosa had only minor effects on the extracellular enzymes and the PA-IL lectin, the production of HCN and pyocyanin was enhanced during the exponential phase. The influence of RsmA on N-acylhomoserine lactone-mediated quorum sensing was determined by assaying the levels of N-(3-oxododecanoyl)homoserine lactone (3-oxo-C12-HSL) and N-butanoylhomoserine lactone (C4-HSL) produced by the rsmA mutant and the rsmA-overexpressing strain. RsmA exerted a negative effect on the synthesis of both 3-oxo-C12-HSL and C4-HSL, which was confirmed by using lasI and rhlI translational fusions. These data also highlighted the temporal expression control of the lasI gene, which was induced much earlier and to a higher level during the exponential growth phase in an rsmA mutant. To investigate whether RsmA modulates HCN production solely via quorum-sensing control, hcn translational fusions were employed to monitor the regulation of the cyanide biosynthesis genes (hcnABC). RsmA was shown to exert an additional negative effect on cyanogenesis posttranscriptionally by acting on a region surrounding the hcnA ribosome-binding site. This suggests that, in P. aeruginosa, RsmA functions as a pleiotropic posttranscriptional regulator of secondary metabolites directly and also indirectly by modulating the quorum-sensing circuitry.